Educational thinking of the 21st century and perseverance of the Malay value - Makmun, Rozaiman; Abu Bakar, Roslina (Human Resource Management Academic Research Society, 2020)
The educational system and philosophy in the Brunei Darussalam has experienced twists and turns of development starting with the time of Resident until it became more intact with the SPN21. Global educational thought emphasizes various criteria such as focus on the students; critical thinking, creativity and innovativeness; thinking out of the box; integration of technology and various skills of the 21st century; planned teaching and learning; dialogical teaching; differential teaching and so on and so forth. This paper work will prove how far the concepts that are presented in the 21st century is in line with the values that has always been the Malay way of thinking. Next, this study will analyze the possibility of the educational thought or ideas of the 21st century bringing universal values until it can be accepted and used by the education system at various countries. The objective of this study will unravel how far the mentioned values and thoughts are in line with the values and thoughts of the Malay people. Next, is to answer if there is any contradiction of the mentioned value and thought with the Malay Islamic Monarchy value that is the philosophy of the Brunei Darussalam. This study uses the text analysis method towards the Malay values that are in the Malay proverb and decree of the Kebawah Duli Yang Maha Mulia Paduka Seri Baginda Sultan Haji Hassanal Bolkiah about self-identity and concept of the Malay Islamic Monarchy.